[PP.30.29] PREHYPERTENSION AND SINGLE NUCLEOTIDE POLYMORPHISM RS13333226 OF THE UROMODULIN (UMOD) GENE. (September 2017) - Domislovic, V.; Dapic, K.; Simicevic, L.; Vrkic, T. Zeljkovic; Josipovic, J.; Laganovic, M.; Fucek, M.; Rogic, D.; Sertic, J.; Jelakovic, A.; Dika, Z.; Kos, J.; et al.
Abstract : Objective: Single nucleotide polymorphism of UMOD gene rs13333226 and its G minor allele were found to be associated with lower blood pressure (BP) values. The aim in this study was to analyze the relationship of this polymorphism with prehypertension (PHT) in general population and here we are reporting preliminary cross-sectional results. Design and method: Out of 3056 subjects enrolled in ENAH study, 496 were eligible for further analysis. Exclusion criteria were treatment with antihypertensive drugs, diabetes, pregnancy, eGFR<60 ml/min, cardiovascular or cerebrovascular incident, chronic terminal diseases, dementia, immobility and missing data. BP and heart rate were measured using Omron 6 device following the ESH guidelines. PHT was defined following the JNC 7 guidelines as a BP >=120/80 and <140/90 mmHg, and normotension (NT) as a BP <120/80 mmHg. Clinical and laboratory data were obtained by routine methods and polymorphism was obtained with TaqMan® real time PCR method. Results: Prevalence of genotypes and G minor allele in overall population were A/A 68.5% (N = 340), A/G 29.6% (N = 147), G/G 1, 8% (N = 9) and G minor allele 16% (N = 165). Distribution of all genotypes and G minor allele did not differ significantly between groups of participants with PHT and NT. Logistic regression showed that none of the observed genotypes were predictors for PHT. Common risk factors such as gender, age and body mass index affect systolic BP and the estimated glomerular filtration in all genotypes equally. Conclusions: We failed to find neither an association of uromodulin gene (SNP rs13333226) with BP in normotensive subjects nor this SNP was predictor of prehypertension. In this ongoing study we will enlarge the sample what might enable us to detect small changes in BP phenotype, and in follow up period will analyze predictive value of this polymorphisms for development of sustained hypertension.